ANALISIS PERSEPSI MANAJEMEN ASET (TANAH DAN BANGUNAN) KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI JAMBI - , Nurlia Fusfita; , Prof. Dr.Iswardino S.Permono, MA., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to analyze the perception of land and buildings asset management by measuring importance level and performance level of asset management important factors that has been implemented by ministry of religious affairs regional office of Jambi province. This research use purposive sampling technique with 84 respondents as sample. Analysis tools used in this research where IPA to measure importance level and implementation performance of asset management key factors for land and building (Martilla & James 1977), and kruskal wallis test to analyze management inter level perception to importance level and performance level of asset management key factors. Research result showed the importance level analysis of the implementation asset management key factors to land and building shows that variable which highest importance level is inventaritation including data collection, recording, and information storage relating with land and building asset answered by respondent average value 4,190 with mode value 5 (very importance). Mean while, performance level analysis of implementation of asset management key factors to land and building shows that inventaritation variable including data collection, recording, and information storage has been properly implemented in a accordance with the expected with highest ranks in which respondent answered this variable with mean value 4,0714 and mode value 4 (good). Variable with lowest performance level is legal audit to land and building asset, which respondent answered this variable with mean value 3,5714 and mode value 4 (good). There is no difference of perception of management inter level in valuing importance level and performance level for implementation of asset management key factors to land and building.